A robotic system for home security enhancement - Michael-Grigoriou, Despina; Gregoriades, Andreas; Michail, Harris; Lesta, Vicky Papadopoulou; Obadan, Samuel (My University, 2010)
Central to smart home security is the need for adequate surrounding awareness. Security systems have been designed for remote exploration and control, however, these still lack the simplicity needed by elderly and disabled. The majority of elderly people find the control of such systems laborious. This highlights the need for usable designs that take into consideration the cognitive limitations of this category of people. This paper contributes towards this problem through the introduction of a novel vehicular Remote Exploration Surveillance Robot (RESBot), capable of monitoring in real time the environment in response to events. The interaction with the system is achieved through natural language commands and hence, provides improved usability over traditional approaches. Results from the experimental usability evaluation of the RESBot system revealed considerable improvement over conventional home security systems. © 2010 Springer-Verlag.
Keywords: Home security; Human-robot interaction; Situation awareness; Teleoperation